Vitamin D and Lifestyle Factors in Active Smoker in Indonesia - Lorensia, Amelia; Suryadinata, Rivan Virlando; Jalmav, Marthy Meliana Ariyanti; Aprianti, Pande Made Ayu; Wati, Angela Nofvianti Cahyo; Dhiba, Zahwa (Universitas Negeri Semarang in collaboration with Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI Tingkat Pusat) and Jejaring Nasional Pendidikan Kesehatan (JNPK), 2025)
Smoking can affect vitamin D levels in the blood. Decrease in vitamin D levels are also influenced by a person's lifestyle habits, such as smoking habits, sun exposure, food intake and physical activity. This study aimed to determine relationship between vitamin D with lifestyle factors in active smoker. This research used cross-sectional design. The subjects were adult male active smokers in Rungkut Subdistrict, Surabaya City, from October 2023 to February 2024. The sampling method was purposive sampling technique. Data collection by measurement of smoking severity (Brinkman Index (BI)), vitamin D levels in blood (serum 25(OH)D), food intake (by SQ-FFQ (semi-quantitative food frequency questionnaire) and 24 hour food recall), and physical activity (by IPAQ (International Physical Activity Questionnaire)). The relationship using Spearman method (ordinal scale). There were 47 respondents. The majority of research respondents were moderate smokers, namely 38 people (80.85%). The respondents had an average 25(OH)D level of 23.19±8.86 ng/mL. The risk of vitamin D deficiency due to lack of sun exposure were 26 people (55.32%). The average consumption of foods containing vitamin D by SQ-FFQ was 5.75±5.68 mcg/day, and 24 hour food recall was 5.77±5.72 mcg/day. Most respondents had high physical activity (70.21%) and total mean was 8210.23±4955.89. The Spearman correlation coefficient was 0.742 (smoking severity), 0.117 (sun exposure), and 0.726 (food intake by FFQ), 0.742 (food intake by 24 hours recall), and 0.824 (physical activity). Vitamin D levels had significant association on severity smoking, food intake and physical activity. However, were not related to sun exposure.